Concise Review: Exploring Immunomodulatory Features of Mesenchymal Stromal Cells in Humanized Mouse Models. (21st December 2018) - Mehler, Vera J.; Burns, Chris; Moore, Melanie L.
Abstract : With their immunosuppressive features, human mesenchymal stromal cells (MSCs), sometimes also termed as mesenchymal stem cells, hold great potential as a cell-based therapy for various immune-mediated diseases. Indeed, MSCs have already been approved as a treatment for graft versus host disease. However, contradictory data from clinical trials and lack of conclusive proof of efficacy hinder the progress toward wider clinical use of MSCs and highlight the need for more relevant disease models. Humanized mice are increasingly used as models to study immune-mediated disease, as they simulate human immunobiology more closely than conventional murine models. With further advances in their resemblance to human immunobiology, it is very likely that humanized mice will be used more commonly as models to investigate MSCs with regard to their therapeutic safety and their immunomodulatory effect and its underlying mechanisms. Recent studies that explore the immunosuppressive features of MSCs in humanized mouse models will be discussed in this review. Stem Cells   2019;37:298–305 : Abstract :